2005
DOI: 10.1242/jcs.02663
|View full text |Cite
|
Sign up to set email alerts
|

Carboxyamidotriazole-induced inhibition of mitochondrial calcium import blocks capacitative calcium entry and cell proliferation in HEK-293 cells

Abstract: Blocking calcium entry may prevent normal and pathological cell proliferation. There is evidence suggesting that molecules such as carboxyamidotriazole, widely used in anti-cancer therapy based on its ability to block calcium entry in nonexcitable cells, also have antiproliferative properties. We found that carboxyamidotriazole and the capacitative calcium entry blocker 2-aminoethoxydiphenyl borate inhibited proliferation in HEK-293 cells with IC50 values of 1.6 and 50 μM, respectively. Capacitative calcium en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 34 publications
4
42
0
Order By: Relevance
“…This is of particular interest considering that CAI is under phase I and phase II clinical trials for the treatment of solid tumors (22,(24)(25)(26)(27). CAI is a nonselective blocker of nonvoltage-gated Ca 2+ channels and it has been shown to inhibit both SOCE and NSOCE (17,(66)(67)(68). In particular, we previously showed that CAI blocks AAinduced NSOCE in normal endothelial cells (17).…”
Section: Discussionmentioning
confidence: 99%
“…This is of particular interest considering that CAI is under phase I and phase II clinical trials for the treatment of solid tumors (22,(24)(25)(26)(27). CAI is a nonselective blocker of nonvoltage-gated Ca 2+ channels and it has been shown to inhibit both SOCE and NSOCE (17,(66)(67)(68). In particular, we previously showed that CAI blocks AAinduced NSOCE in normal endothelial cells (17).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, in cells with de-energized mitochondria and reduced mitochondrial Ca 2+ uptake, the elevated [Ca 2+ ] i maintains storeoperated channels closed, consistent with the Ca 2+ -dependent inactivation of I CRAC (Hoth, et al, 2000, Parekh, 1998. As mitochondria have the potential to regulate intracellular Ca 2+ signalling and determine the transcriptional potential of a cell (Hoth, et al, 2000), targeting mitochondria has recently been exploited to control I CRAC -mediated Ca 2+ influx and associated cell proliferation (Enfissi, et al, 2004, Holmuhamedov, et al, 2002, Mignen, et al, 2005, Nunez, et al, 2006. Drugs such as carboxyamidotriazole (CAI) or salicylate, which inhibit mitochondrial calcium import (Mignen, et al, 2005, Nunez, et al, 2006, or diazoxide, which displays a predilection for the inner mitochondrial membrane (Holmuhamedov, et al, 2002), can arrest cell cycle progression and block cell proliferation.…”
Section: Mitochondrial Calcium and Cancermentioning
confidence: 92%
“…For mitochondrial calcium analysis, the fluorescence of Rhod-2 was recorded during consecutive 500-ms pulses at 550/590 nm excitation/emission. Rhod-2 fluorescence was analyzed by selecting regions of interest where MitoTracker Green and Rhod-2 co-localized (43). Fluorescence intensity at each time (F t ) was calculated after correcting for background and differential bleaching.…”
Section: ϫ/ϫmentioning
confidence: 99%